ASEAN-5+3 and US stock markets interdependence before, during and after Asian financial crisis - R. C., Royfaizal; Lee, Chin; Mohamed, Azali (Canadian Center of Science and Education, 2009)
The issues of international stock markets linkages had been investigated over the time. Since the Asian financial crisis in 1997, many economists are concerned about the relationship between Asian stock markets and others in the world. The main objective of this paper is to examine the linkages between ASEAN-5+3 namely Malaysia, Singapore, the Philippines, Thailand, Indonesia, China, Japan and Korea an d US stock markets. The data consists of weekly stock indices data. The total samples are separated into three sub-periods. All the indices applied are expressed in local currencies. In conclusion, we found that ASEAN-5+3 and US stock markets are interdependence during crisis and post-crisis periods and the impact of US stock market is effective in ASEAN-5+3 stock markets only for pre- and during-crisis periods.